2004
DOI: 10.3758/bf03196039
|View full text |Cite
|
Sign up to set email alerts
|

Stable individual differences on developmental tasks in young yellow-crowned parakeets,Cyanoramphus auriceps

Abstract: We report on stable individual differences in young yellow-crowned parakeets across 38 tasks of cognitive development on three scales involving object permanence, means-end relations, and spatial relations. Stable performance ranks on blocks of tasks emerged after 13 weeks in two groups of sibling parakeets, one hand-reared and the other parent-reared. Examination of subject characteristics, such as hatch order, sex, general activity level, avoidances, latencies, social status, and errors, showed no significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This does not mean, however, that more distantly related species are unsuitable -only that the tests must be adapted to enable comparison. For example, Funk (1996aFunk ( , 1996bFunk ( , 2002Funk & Matteson, 2004) investigated the development of yellow-crowned parakeets (Cyanoramphus auriceps) in several Piagetian domains and found consistent individual performance and a development pattern similar to that of human infants. Although the parakeets developed much faster, the precise timing of their development, resulting from various performance factors, is relatively unimportant.…”
Section: Sensorimotor Cognition and Developmentmentioning
confidence: 99%
“…This does not mean, however, that more distantly related species are unsuitable -only that the tests must be adapted to enable comparison. For example, Funk (1996aFunk ( , 1996bFunk ( , 2002Funk & Matteson, 2004) investigated the development of yellow-crowned parakeets (Cyanoramphus auriceps) in several Piagetian domains and found consistent individual performance and a development pattern similar to that of human infants. Although the parakeets developed much faster, the precise timing of their development, resulting from various performance factors, is relatively unimportant.…”
Section: Sensorimotor Cognition and Developmentmentioning
confidence: 99%
“…In this case, rearing history may have influenced the level of novel object apprehension in this highly neophobic species. It has, for example, been shown that hand-reared juvenile orange winged amazons and New Zealand parakeets approach novel objects faster than parent-reared birds (Fox & Millam, 2004; Funk, 2002; Funk & Matteson, 2004). Nevertheless, it is curious that the remaining subjects did not even leave their perches throughout most of the entire experiment (15 sessions of 30 minutes).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also investigated personality in fish, birds, reptiles, amphibians, and insects (e.g. fish: Coleman & Wilson, 1998;Francis, 1990;Budaev, 1997;birds: Webster & Hurnik, 1990;Jones et al, 1991;Figueredo et al, 1995;Funk & Matteson, 2004;snakes: Herzog & Burghardt, 1988;newts: Halliday, 1976;butterflies: Gerould, 1927). For example, Budaev (1997) examined differences in the exploratory behavior and social tendencies of guppies.…”
Section: Non-mammalsmentioning
confidence: 99%